2013
DOI: 10.1542/peds.2013-0163
|View full text |Cite
|
Sign up to set email alerts
|

Firearm Possession Among Adolescents Presenting to an Urban Emergency Department for Assault

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Violence involving firearms is a leading cause of death among US youth ages 14 to 24. The emergency department is the primary medical setting for care of assault-injured youth and an underused but important setting for violence-prevention programs.WHAT THIS STUDY ADDS: Among assault-injured youth seeking emergency department care, firearm possession rates are high, most obtained outside of legal channels. Higher rates of negative retaliatory attitudes and substance use among those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 64 publications
4
87
0
Order By: Relevance
“…This may be explained by higher rates of retaliatory attitudes (32) and easier access to firearms (33) in children of this age category. Therefore, educating the families regarding safe storage of the firearms is very important.…”
Section: Discussionmentioning
confidence: 96%
“…This may be explained by higher rates of retaliatory attitudes (32) and easier access to firearms (33) in children of this age category. Therefore, educating the families regarding safe storage of the firearms is very important.…”
Section: Discussionmentioning
confidence: 96%
“…Direct literature comparisons are limited because this longitudinal study, to our knowledge, is the first to comprehensively characterize such a broad range of firearm violence outcomes among a systematically sampled cohort of assault-injured youth. Observed rates of firearm behaviors, however, are higher than those in national adolescent samples, 50,51 as well as in previous ED-and school-based studies that have focused on either violent injury recidivism 19,[52][53][54] or examined surrogate markers (eg, firearm possession/carriage; severe peer violence) 13,46,55,56 for firearm violence. Our results highlight that an ED assault-injury visit is an important indicator of future firearm violence risk and emphasize the substantial need for evidence-based interventions addressing this risk.…”
Section: Discussionmentioning
confidence: 92%
“…As in previous work, 13 past 6-month firearm possession was a composite of 5 measures from the Tulane Study 41,42 characterizing firearm ownership/carriage. Measures excluded hunting or sporting activities.…”
Section: Firearm Carriage and Possessionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunningham et al [20] found that 1/5 of adolescents recruited through the urban ED reported carrying a weapon. Carter et al [21] found high rates of firearm possession among assault-injured youth, with nearly 1 in 4 reporting possession, and 42% of those with firearms carrying the weapon outside the home; additionally, 32% of these assault-injured youth with firearms were also parents, raising questions about safe firearm storage within the home. However, an examination substance use and violence among a general sample of adolescent parents who utilize emergency department (ED) services is understudied.…”
Section: Screening Adolescent Parents Through the Emergency Departmentmentioning
confidence: 99%